Biochemical Study on Pleural Effusion Fluid in Tuberculous and non-Tuberculous in Iraqi Patients - Ali, Lara; Salih, Dhuha; Mankhi, Ahmed (Iraqi Journal of Science, 2023)
Seventy exudative lymphocytic pleural fluid specimens of patients with suspected tuberculous pleural effusion submitted to the National Reference Laboratory of tuberculosis/Baghdad from October 2012 to February 2013. These effusions were due to tuberculosis pleuritis (n=12) and non-tuberculosis pleuritis (n=58). The following parameters were analyzed: protein concentration, glucose concentration, lactate dehydrogenase (LDH) concentration and adenosine deaminase activity (ADA). As a result, the protein concentration was higher in TPE patients (8.80 ± 0.89 g/dl) than it’s concentration in non-TPE patients (7.61 ± 0.54 g/dl), as well as LDH concentration was (3366.58 ± 284.28 U/L) in TPE patients and (3024.12 ± 116.84 U/L) in non-TPE patients and ADA activity was higher in the TPE patients (226.05 ± 16.90 U/L) than (153.06 ± 9.37 U/L) in non-TPE too. Whereas glucose was the unique parameter that it’s concentration is lower in TPE patients than it’s concentration in non-TPE patients (27.23 ± 4.81 mg/dl) and (199.80 ± 18.51 mg/dl) respectively. As a conclusion, the combination of the two parameters, protein level > 5 g/dl and glucose level < 60 mg /dl may be diagnostic for tuberculous pleural effusion. The higher level of ADA, greater the chance of the patient having TB while lower the level lesser the chance of the patient having TB. LDH measurement is a sensitive, but rather non-specific inflammatory marker.